Development of stabilization treatment technology for radioactive aluminum waste - SANO, Tadafumi; SEKI, Misaki; OMORI, Takazumi; YOSHINAGA, Hisao; FUJIHARA, Yasuyuki; NAGATA, Hiroshi; J., Zhang; HORI, Junichi; TSUCHIYA, Kunihiko; OTSUKA, Kaoru; FUJITA, Yoshitaka; TAKEUCHI, Tomoaki; et al. (Journal of Nuclear Fuel Cycle and Environment, 2022)
The core structural materials of the Japan Materials Testing Reactor (JMTR) are mostly stainless steel, aluminum (Al) and beryllium (Be). In the decommissioning of JMTR, radioactive miscellaneous solid wastes (waste packages) are produced. The burial criteria require that the drums do not contain any materials that would impair the integrity of the drums, and that the radioactivity of the waste packages does not exceed the amount specified in the criteria. In particular, Al generates hydrogen gas when it reacts with alkaline substances. This can cause voids to form inside the waste package, reducing its strength and increasing the internal pressure, causing the solidifier to overflow. Such a waste package will affect the safe management of the facility. The purpose of this paper was to establish a stabilization treatment technology for Al by applying the Beyer process, and the basic treatment process was established through cold tests. The Al samples were irradiated with neutrons at the Kyoto University Research Reactor (KUR) to investigate the removal characteristics of radionuclides produced by additive and impurity elements in Al by this process. As a result, it was found that Al can be converted to alumina (Al2O3) by this process, and there is a prospect that it can be solidified by cement-based filler as in the usual treatment method for radioactive waste.